Comparative Analysis of the Size of Glass Fiber Woven Roving based on a Polyester Matrix on the Impact Strength of Composite Materials - M. Fajar Lazuardy; Muhammad Fakhruddin (Universitas Sebelas Maret, 2024)
Laminated Glass Fiber Reinforced Polymer (GFRP) composites are widely used in various industries, such as boat building, car bodies, water tanks and pipelines, which in their use sometimes have the potential to be exposed to impact loads, especially in transportation equipment. Therefore, it is necessary to perform an impact test to determine the toughness value of a composite material against impact loads. This study aims to investigate the characteristics of fibreglass Woven Roving (WR)/polyester composites produced by the compression moulding process to determine the toughness of the composite material concerning changes in weave size. This research uses variations of glass fibre woven roving in sizes of 200 gsm, 400 gsm, 600 gsm. The impact test was conducted following the American Society for Testing Materials (ASTM) D6110-10. The impact test result showed that the lowest impact strength is found in a composite with a woven size of 200 gsm, which is 0.145 J/mm2, and the highest impact strength is found in composite with a woven size of 600 gsm, which is 0.280 J/mm2.